Sistema web de gestión y control de procesos en los laboratorios de prácticas en las UDIV de la carrera de Computación - Cobeña Armijos, Yelena Paola (2023)
The purpose of the curricular integration work was to develop a web process management system in the laboratories of the UDIV of the Computing career of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López for the efficient administration of information, the system was developed with the XP (Extreme Programming) methodology that consists of four phases: planning, design, coding and testing; in the planning, the realization of the user stories and the elaboration of the guidelines proposed by the IEEE 830 standard were carried out; Similarly, in the design phase, the Class Responsibility Collaboration cards and the design of the system interfaces were made; Regarding the coding phase, this was developed using the PHP programming language with the Laravel Framework, while JavaScript was used for the client part with the Angular Framework; in the testing phase, the correct functioning of the system was verified through unit tests and black box tests; As a result, a web system was obtained that allows reserving different laboratories at certain times and keeping track of the instruments and supplies through the inventory; in addition, a management of reports referring to the planned practices and a virtual repository that allows attaching the information through a friendly interface.